The Influence of Tourism Products and Promotion on Tourists' Visiting Decisions to A Water Park in Karawang - Riady, Alya Astrid; Suleman, Eman (Universitas Mercu Buana, 2024)
This study aims to determine the effect of tourism products and promotions on tourists' visiting decisions at Waterpark and to test and analyze tourism products and promotions on tourists' visiting decisions at Waterpark. The data were analyzed using path analysis and hypothesis testing using the t test and f test. Based on the results of the descriptive analysis of Tourism Products, it obtained an average score of 390.63 with the criteria for agreeing, Promotion got an average score of 347.71 with the criteria for agreeing, then on Customer Satisfaction it got an average score of 345.44 with the criteria for agreeing. Respondents analyzed tourism products and promotions on the decision to visit tourists a water park in Karawang which was good. Based on the results of the Tourism Product verification analysis with Promotion, it has a correlation of 0.640 and has a strong correlation level. Partially, it shows that price has an influence on tourists' visiting decisions, which is equal to 10.44%, this shows that the product has an effect on the decision to visit a water park in Karawang. Then, for the results of the partial research promotion of the decision to visit, which is equal to 51.78%, this shows that the promotion of the decision to visit at a water park in Karawang. While the simultaneous effect of tourism products and promotions on tourists' visiting decisions is equal to 62.22%, while the influence of other variables outside the research model is equal to 37.78%.